2019
DOI: 10.1681/asn.2018101017
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in IgA Nephropathy: A Nationwide Population-Based Cohort Study

Abstract: BackgroundThe clinical course of IgA nephropathy (IgAN) varies from asymptomatic nonprogressive to aggressive disease, with up to one in four patients manifesting ESRD within 20 years of diagnosis. Although some studies have suggested that mortality appears to be increased in IgAN, such studies lacked matched controls and did not report absolute risk.MethodsWe conducted a population-based cohort study in Sweden, involving patients with biopsy-verified IgAN diagnosed in 1974–2011; main outcome measures were dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 42 publications
5
83
0
2
Order By: Relevance
“…These deficiencies may have a bearing on the observation that excess mortality was limited to individuals with IgAN and ESRD, a somewhat paradoxical finding considering that large epidemiologic studies have shown that mortality risk increases as stage of "generic" CKD (as defined by Kidney Disease Improving Global Outcomes [KDIGO] criteria) increases, well before ESRD has developed. 6 A comparison with prior reports may provide some insight into some of the perplexing findings of the study by Jarrick et al 5 Knoop et al 4 conducted a nationwide, registry-based cohort study in Norway involving 663 subjects with biopsyproven IgAN followed for a median of 11.3 years. The subjects were an average age 39 years old, and 74% were men.…”
Section: Zhao F Zhu J-y Richmanmentioning
confidence: 97%
See 3 more Smart Citations
“…These deficiencies may have a bearing on the observation that excess mortality was limited to individuals with IgAN and ESRD, a somewhat paradoxical finding considering that large epidemiologic studies have shown that mortality risk increases as stage of "generic" CKD (as defined by Kidney Disease Improving Global Outcomes [KDIGO] criteria) increases, well before ESRD has developed. 6 A comparison with prior reports may provide some insight into some of the perplexing findings of the study by Jarrick et al 5 Knoop et al 4 conducted a nationwide, registry-based cohort study in Norway involving 663 subjects with biopsyproven IgAN followed for a median of 11.3 years. The subjects were an average age 39 years old, and 74% were men.…”
Section: Zhao F Zhu J-y Richmanmentioning
confidence: 97%
“…Factors that enhance the likelihood of progression and the risks of ESRD have been well studied, but the risks of mortality after long periods of follow-up are less well understood. 2 The gaps in our understanding of the pattern of mortality associated with a diagnosis of IgAN have been lessened by several large observational cohort studies (single center or registry based) with long-term follow-up, 3,4 including one published in this issue of the Journal of the American Society of Nephrology by Jarrick et al 5 Although each of these studies has varied somewhat in the design, they provide substantial support for the conclusion that a diagnosis of IgAN is associated with shortened life expectancy. Although in and of itself, this is not surprising, the details of these studies provide some interesting insights into the nature of this enhanced mortality risk in IgAN and raise several new questions-all hallmarks of excellent clinical research.…”
Section: Zhao F Zhu J-y Richmanmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a very common form of primary glomerulonephritis that affects about 200,000–350,000 people per year globally [3]. Its diagnosis is associated with a reduction in life expectancy between 6 and 10 years [4]. Its incidence has also been associated with poor socioeconomic situations [5].…”
Section: Introduction Iga Nephropathy Overviewmentioning
confidence: 99%